Somatotype Pemain Bola Voli Indoor Putra Pekan Olahraga Mahasiswa Nasional Kontingen Sumatera Barat - Muhamad Sazeli Rifki; Arif Rahmat; Wilda Welis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the somatotype of indoor men's volleyball players national sports week contingent of West Sumatra in 2019. The measuring instrument used in this study uses a scale to measure weight, a meter to measure height, skinfold caliper to measure fat thickness, calipers to measure the width of bones and lila bands to measure the circumference of the arms and calves. This research is descriptive research. The method used is a survey method with data collection techniques using anthropometric tests and measurements. The population in this study were 14 male indoor volleyball players. the data analysis technique used descriptive percentage analysis. The results of this study show that male indoor volleyball somatotype players have 7 players somatotype or body type mesomorph ectomorph or 50%, mesomorphic ectomorph body type as many as 5 players or 36%, balanced ectomorph body type as much as 1 player or 7%, and body type ectomorph as many as 5 players Endomorphic ectomorph body as much as 1 player or 7%. In conclusion, the indoor men's volleyball player at the National Student Sports Week is already suitable for volleyball. Keywords: Somatotype, Volleyball, POMNAS